(untitled) (Journal of Medical & Health Sciences Review, 2025)
Human Papillomavirus (HPV) is commonly linked with both benign conditions such as skin, oral, and anogenital warts, and malignant diseases including cervical, oral cavity, and ovarian cancers. While sexual contact remains the primary transmission route, vertical, horizontal, and auto-inoculation pathways also exist. A possible link between high-risk HPV strains and spontaneous abortion has been suggested.This cross-sectional study was conducted at Hayatabad Medical Complex, Peshawar, over 1.5 years. A total of 120 placental samples were collected from women who experienced spontaneous abortion before 24 weeks of gestation. Samples underwent Polymerase Chain Reaction (PCR) testing to detect HPV types 16 and 18, and histopathological examination was performed using Hematoxylin and Eosin (H&E) staining.All placental samples tested positive for beta-globin, confirming sample integrity, but none were positive for HPV DNA. While classic koilocytosis was absent, some histological features such as bi-nucleation, multi-nucleation, and perinuclear halo were observed. A key limitation was the large size of placental tissue, which restricted complete analysis.No evidence of HPV DNA was found in placentas from spontaneous abortions, suggesting no direct association in this cohort.